Basal Ganglia Mineralization in Alzheimer’s Disease: A Comparative Study of Clinical, Neuroradiological and Neuropathological Findings - H. Förstl; A. Burns; N. Cairns; P. Luthert; R. Levy (Behavioural Neurology)
Fifty patients from a longitudinal study on 178 cases of Alzheimer's disease were examined at postmortem. The clinical features, CT-scans and neuropathological findings of five patients, with verified Alzheimer's disease, who had bilateral basal ganglia mineralization (BGM; 2 male, 3 female; age 78–91 years) were compared with the data of five age- and sex-matched Alzheimer patients without BGM and of five control subjects. Persecutory and other delusions (4 patients), persistent depression (2), parkinsonism (4), myoclonus (1) and epileptic seizures (1) were observed more frequently in the patients with BGM than was expected. The BGM-group had significantly lower counts of large neurons in the pallidum internum than the demented patients without BGM or the control group. We did not find other differences between the dementia groups regarding the CT-scans, or plaque, tangle and neuron counts in neocortex and brainstem. We suggest that the combined effects of Alzheimer pathology and BGM might lead to an increased manifestation of psychotic and motor disturbances.